Mass media as forum for political debate. Diversity in Danish newspaper coverage of the first political festival in Bornholm - Laursen, Bo; Trapp, N. Leila (Politica, 2015)
According to normative theories on the public sphere and democracy, inclusive public debates should take place in deliberative democracies, such as Denmark’s, before political decisions are made. These debates, which in Denmark currently mostly take place via the mass media, are intended to ensure that all viewpoints and arguments are considered in the decision making process, so that the public can gain influence and ownership of the decisions. To determine the extent to which the media facilitates public debates that are inclusive, we examined whose viewpoints were presented in the large Danish newspapers’ coverage of a recent political event: the 2011 political festival in Bornholm. We found that the coverage was heavily dominated by politicians’ viewpoints, and that average citizen viewpoints were very infrequently included.